Students’ Application of Systematic Functional Linguistics on EFLs’ Blog Website - Seriani Hutasuhut; Octa Vina Harahap (English Education : English Journal for Teaching and Learning, 2021)
The study aims to investigate the Systemic Functional Linguistics (SFL) as a method for analyzing text. The Systemic Functional Linguistics (SFL) has a nearly limitless range of applications. Social media has become an important platform for everyone to broadcast information, opinions, and emotion freely and borderless in today's society especially on blog. Using a qualitative method, this research focused on the outcome of the students’ ability in applying SFL on social media. The data are taken from Blog-Web media of English Education Department Students IAIN Padangsidimpuan. The findings lead to the conclusion that the application of Systemic Functional Linguistics on Blog was good. Interpersonal meaning occurred in 9 times or in percentages of 45% of written clauses entires. It signifies that its ability to inform and persuade readers goes optimal. However, linguistic approaches must be improved in order for the texts to sound more understandable.